Terahertz Modulator Using 4-N,N-Dimethylamino-4′-N′-Methyl-Stilbazolium Tosylate (DAST)/Si Hybrid Structure - Li Jiu-sheng; Li Shao-he; Zhang Le (IEEE Photonics Journal, 2018)
Terahertz high-data communication creates numerous demands for terahertz wave amplitude modulation. Here, we experimentally demonstrate a high-speed terahertz wave modulator based on 4-N,N-dimethylamino-4'-N'-methyl-stilbazolium tosylate (DAST)/Si hybrid structure. An externally modulated 808-nm pumping laser is utilized to generate photoexcited free carriers at the DAST medium. With the increase of illumination laser intensity, the modulation depth continues to increase in the frequency range from 0.23 to 0.35 THz. A dynamic amplitude modulation at 0.25-THz carrier wave shows that the our modulator provides a modulation speed of 1.26 MHz with a depth of up to 53% at an external pump laser irradiance of 3.5 W/cm2. Our present DAST/Si hybrid structure provides a practicable route to achieve effective signal modulation for terahertz communication system.